The structure of gravel‐bed flow with intermediate submergence: A laboratory study. Issue 11 (28th November 2015) - Mohajeri, S. H.; Grizzi, S.; Righetti, M.; Romano, G. P.; Nikora, V.
Abstract: The paper reports an experimental study of the flow structure over an immobile gravel bed in open channel at intermediate submergence, with particular focus on the near‐bed region. The experiments consisted of velocity measurements using three‐component (stereoscopic) Particle Image Velocimetry (PIV) in near‐bed horizontal plane and two‐component PIV in three vertical planes that covered three distinctly different hydraulic scenarios where the ratio of flow depth to roughness height (i.e., relative submergence) changes from 7.5 to 10.8. Detailed velocity measurements were supplemented with fine‐scale bed elevation data obtained with a laser scanner. The data revealed longitudinal low‐momentum and high‐momentum "strips" in the time‐averaged velocity field, likely induced by secondary currents. This depth‐scale pattern was superimposed with particle‐scale patches of flow heterogeneity induced by gravel particle protrusions. A similar picture emerged when considering second‐order velocity moments. The interaction between the flow field and gravel‐bed protrusions is assessed using cross correlations of velocity components and bed elevations in a horizontal plane just above gravel particle crests. The cross correlations suggest that upward and downward fluid motions are mainly associated with upstream‐facing and lee sides of particles, respectively. Results also show that the relative submergence affects the turbulence intensity profiles for vertical velocity over the whole flow depth, while only a weak effect, limited to the near‐bed region, is noticed for streamwise velocity component. The approximation of mean velocity profiles with a logarithmic formula reveals that log‐profile parameters depend on relative submergence, highlighting inapplicability of a conventional "universal" logarithmic law for gravel‐bed flows with intermediate submergence. Key Points: Formation of secondary currents in wide open‐channel with rough bed Quantifying correlation of bed elevation and time‐averaged flow field Importance of relative submergence in turbulent flow characteristics